2013
DOI: 10.1111/pme.12065
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Radiation-Induced Proctitis Pain by Blockade of the Ganglion Impar in an Elderly Patient with Prostate Cancer: A Case Report

Abstract: Based on this case's success, a prospective study or randomized control trial evaluating the efficacy of the ganglion impar block as a treatment option for chronic anorectal pain secondary to radiation-induced proctitis appears warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[ 76 ] Patients often complains of burning sensation or urinary and rectal urgency with ganglion impar associated dysfunction. [ 8 ] Other indications include radiation induced proctitis (rectal pain),[ 77 ] coccygodynia, perianal sweating, and tenesmoid pain. [ 78 ] Plancarte first described the technique for fluoroscopic-guided Ganglion impar block by introducing a bent needle through anococcygeal membrane with a finger inserted in the rectum to guide the needle and prevent rectal injury.…”
Section: Interventional Pain Management Guidelines According To Clinimentioning
confidence: 99%
“…[ 76 ] Patients often complains of burning sensation or urinary and rectal urgency with ganglion impar associated dysfunction. [ 8 ] Other indications include radiation induced proctitis (rectal pain),[ 77 ] coccygodynia, perianal sweating, and tenesmoid pain. [ 78 ] Plancarte first described the technique for fluoroscopic-guided Ganglion impar block by introducing a bent needle through anococcygeal membrane with a finger inserted in the rectum to guide the needle and prevent rectal injury.…”
Section: Interventional Pain Management Guidelines According To Clinimentioning
confidence: 99%
“…Previous studies have shown the effectiveness of ganglion impar block [4][5][6] and radiofrequency thermocoagulation [7] in patients with chronic coccydynia. In addition, ganglion impar block [8,9] and radiofrequency thermocoagulation [10] for perianal pain may also be effective in decreasing pain intensity. Furthermore, there are several case reports which revealed that ganglion impar block may be useful in managing genital pain [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, blocking the ganglion impar attenuates this sympathetically mediated pain, leading to a reduction of opioid consumption, lessens constipation, and an improvement in the patients’ quality of life. [4]…”
Section: Introductionmentioning
confidence: 99%